A review: Resistant starch, a promising prebiotic for obesity and weight management. (December 2022) - Thompson, Mayrilyn Solo; Hui Yan, Tan; Saari, Nazamid; Sarbini, Shahrul Razid
Abstract: Obesity has become an epidemic where it happens drastically among developing countries. Studies suggested that dietary intake are able to influence human health issues including obesity. Prebiotics are food ingredients that can positively contribute to human health by influencing the balance in gut microbiota. Thus, prebiotic dietary can selectively stimulate the growth of beneficial bacteria in the gut, which could be a strategy to address obesity issues. This includes resistant starch (RS), which is a fermentable prebiotic ingredient that is able to contribute in colonic health. Therefore, it is reviewed in this article that RS as a soluble fiber with prebiotic potential for its ability to resist digestion and passes through the colon as well as positively stimulating the fermentation of gut microbiota. Also, metabolites from the colonic fermentation of RS have been exhibited in many studies. Whereby, it is reported that RS stimulates the gut signaling hormones that are responsible for controlling food appetite, preventing fat accumulation and thus, helps in body weight management. With this knowledge, this review suggested that RS may be an option to combat the development of obesity. Graphical abstract: Image 1 Highlights: Resistant starch (RS) as a prebiotic dietary helps to control the development of obesity. RS prevents obesity through positively stimulating fermentation by gut microbiota. Metabolites from fermentation of RS stimulates gut signalling hormones for appetite. Gut fermentation of RS as prebiotic thus indirectly prevents fat accumulation. Gut fermentation of RS as prebiotic indirectly helps in managing body weight.